Numerical investigation of top-seat angle connections at elevated temperatures / Leong Siong Hean - Leong, Siong Hean (2013)
Significant studies have been conducted for beams and columns in fire. However, studies of connections in fire is comparatively less, although being the more critical component in a steel structure. In addition, the behavior of top-seat angle connection type is still not fully understood in an elevated temperature conditions and subsequently the effect of axial loadings due to steel expansion in fire have also yet to be studied. Very limited experimental data was available for top-seat angle at elevated temperature, which resulted in limited design guideline for this type of connection. Thus, a finite element model for top-seat angle connection at elevated temperature is developed in this study using ANSYS Workbench and validated with existing test results. Models geometry was developed in Solidworks, which was then imported into Hypermesh for the meshing process, followed by detail analysis in ANSYS Workbench. Non-linear behavior of the materials was modeled with the definition of elastic-plastic multi-linear properties and frictional contact between surfaces is included to simulate actual connection behavior. 3D Solid Elements was used in the model. Elevated temperature models are analyzed using the Static Structural option which is shown to be able to simulate elevated temperature conditions. The validation of the ambient temperature models shows that the parameters and techniques used are accurate and in good agreement with experimental results. The validated ambient temperature models are further used for parametric studies on the effect of seat angles, gaps and angle length.Comparison of models at elevated temperature with experimental data shows that the model is in good agreement with existing behavior results of top-seat angle connection tests and therefore the model is used for further study on the effect of axial restraints towards connection behavior. For ambient temperature conditions, Increase in axial restraints has been shown to increase connection capacity while the stiffness remains similar for low axial levels, where at 10% axial restraint, the corresponding moment capacity is increased by 89% and 10% in axial release relates to the same amount in capacity reduction. On the other hand, the shrinkage of the beam, may lead to axial releases, causing axial “pulling” on the connection caused by the catenary action of beams under loads, resulting in higher deformation and different deformation patterns of the connection. Axial release under anisothermal conditions leads to a 28% reduction in resistive temperatures for 10% in axial release levels. In terms of isothermal conditions, the axial restraints are increased by 60% at the lowest temperature for 10% axial restraint and 300% increase of moment capacity under elevated temperature of 600°C. Comparisons with the guidelines provided by EC3 has also been made and the study show that the design guidelines needs further verifications, on parameters including the gap effect, seat angle effect, axial loading design and the angle section length used.